Geo-Congress 2014 keynote lectures : geo-characterization and modeling for sustainability : proceedings of the 2014 Congress, February 23-26, 2014, Atlanta, Georgia - Puppala, Anand J.; Bandini, Paola; Sheahan, Thomas C. (American Society of Civil Engineers, 2014)
This Geotechnical Special Publication contains eight peer-reviewed keynote papers on cutting edge aspects of sustainability-related geotechnical issues. These papers serve as important references and milestones for fast-moving and impactful aspects of geotechnical and geoenvironmental engineering and will be of interest to both practitioners and researchers. -- Provided by publisher.
Keywords: Environmental geotechnology -- Congresses.; Geotechnical engineering -- Congresses.; elektronické knihy; electronic books